2019
DOI: 10.1111/jep.13325
|View full text |Cite
|
Sign up to set email alerts
|

Decisional needs assessment of patients with complex care needs in primary care

Abstract: Rationale Patients with complex care needs who frequently use health services often face challenges in managing their health and with integrated care, leading to frequent decision making. These complex care needs require a good understanding of health issues and their impact on daily life. As the decisional needs of this particular clientele have yet to be described in scientific literature, they warrant further study. Objectives To assess the decision‐making needs of patients with complex care needs (PCCN) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…Sie konstatieren Schwierigkeiten bei Kommunikation und Kooperation an den ambulant-stationären sowie an den hausärztlich-fachärztlichen Schnittstellen, insbesondere in der Versorgung älterer und multimorbider Patienten [9]. Das Zusammenwirken von physischen, psychologischen und sozialen Problemen mit Verlust von Selbstständigkeit und Autonomie führen oftmals zu unadressierten, komplexen Bedarfen und einem erhöhten Auf-wand für die Koordinierung der Inanspruchnahme verschiedenster Versorger [10,11].…”
Section: Zusammenfassungunclassified
“…Sie konstatieren Schwierigkeiten bei Kommunikation und Kooperation an den ambulant-stationären sowie an den hausärztlich-fachärztlichen Schnittstellen, insbesondere in der Versorgung älterer und multimorbider Patienten [9]. Das Zusammenwirken von physischen, psychologischen und sozialen Problemen mit Verlust von Selbstständigkeit und Autonomie führen oftmals zu unadressierten, komplexen Bedarfen und einem erhöhten Auf-wand für die Koordinierung der Inanspruchnahme verschiedenster Versorger [10,11].…”
Section: Zusammenfassungunclassified
“…This paper objective is to enhance the current literature and to provide examples of day-to-day pre, per, and post POR activities. With a view of sharing our knowledge and contributing to improve training programs on POR, we present the POR strategies we used from a collaborative experience in a multicenter qualitative research project (Poitras et al, 2020). The present paper reports POR and lessons learned that emerged from a research project conducted between 2017 and 2019.…”
Section: Objectivementioning
confidence: 99%
“…21 Understanding and assessing the decision making needs not only of patients, but also of their caregivers and health providers in home care, will inform us about ways to better engage older adults and their caregivers in SDM, and how healthcare providers’ can better support them to make decisions together that best reflects their preferences. Numerous studies have assessed the decisional needs of specific populations, such as patients needing complex care, 22 those with heart disease, 23 advanced kidney disease 24 and psoriasis. 25 However, no studies that assess the decisional needs of older adults receiving home care were identified in a recent systematic review.…”
Section: Introductionmentioning
confidence: 99%